Antimalarial drug development: Past to present scenario - Dhanawat M.; Das N.; Ramesh C.; Nagarwal; Shrivastava S.K. (My University, 2025)
Malaria is a global health problem that needs attention of drug discovery scientists to investigate novel compounds with high drug efficacy, safety and low cost to counter the malaria parasites that are resistant to existing drug molecules. This is an overview of past to present status of antimalarial drugs including newly researched candidates and also the alternative approaches for the complete control of malaria. © 2009 Bentham Science Publishers Ltd.